The relationship between depression, anxiety, personality traits and coping strategies of patients with euthyroid Hashimoto's Thyroiditis - YILDIZ, MESUT (EUROPEAN JOURNAL OF PSYCHIATRY, 2017)
Background and objectives: We aimed to investigate the depression and anxiety levels and to explore the coping strategies and personality traits of patients with euthyroid Hashimoto Thyroiditis (HT). Methods: The study population consisted of 108 outpatients with euthyroid HT. The participants completed the Hospital Anxiety and Depression Scale (HADS), the Big Five Personality Inventory (BFI), and the Coping With Problems Experienced Inventory (COPE). Results: Depression scores were negatively correlated with emotion-focused and problem-focused coping style scores. Emotion-focused and problem-focused coping style scores Were negatively correlated with neuroticism, and positively correlated with openness scores. Emotion-focused coping style scores were also positively correlated with agreeableness scores. Dysfunctional coping style scores were negatively correlated with conscientiousness scores. Higher agreeableness and anxiety scores as well as lower neuroticism scores were predictive of emotion-focused coping style scores. Problem-focused coping style scores were predicted by lower depression scores. Dysfunctional coping style scores were predicted by lower conscientiousness scores. Conclusions: The present study points the importance of taking personality features and individual coping strategies into account when evaluating patients with HT. Determining the personality features and coping strategies might be useful for identifying patients in need of particular counseling and support. (C) 2017 Asociacion Universitaria de Zaragoza para el Progreso de la Psiquiatria y la Salud Mental. Published by Elsevier Espana, S.L.U. All rights reserved.
Keywords: Hashimoto Thyroiditis; Personality; Coping strategy; Anxiety; Depression; SEX-DIFFERENCES; AUTOIMMUNITY; DISORDERS; INVENTORY; SYMPTOMS; STRESS; MODEL